Pengembangan E-Pub Untuk Administrasi Sistem Jaringan - Chandra Setia Rini; Nurmida Catherine Sitompul; Yoso Wiyarno (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
Learning in vocational schools is a vocational education has its own characteristics. Network System Administration (ASJ) subjects in Computer and Network Engineering (TKJ) competencies learn about procedures how a computer can act as a server so it requires accuracy to configure network services according to procedure. The purpose of this study is to find the effectiveness of ePub digital book development as a teaching material in the learning process. Development of ePub digital books using ADDIE models with descriptive data analysis techniques. The results of the or validation of the feasibility of product development are content experts / TKJ by 90.67%, learning media experts by 90.52%, and learning design experts by 96%. Product evaluations to users (students) through a questionnaire get a very good response. Product trials that have been carried out can increase the effectiveness of learning by increasing student final test scores. So it can be concluded that the product that has been developed is feasible to use in learning Network Administration System.